Development of novel passive check valves for the microfluidic CD platfor - Al-Faqheri, W.; Ibrahim, Fatimah; Thio, T.H.G.; Aeinehvand, M.M.; Arof, Hamzah; Madou, M. (Elsevier, 2015)
Microfluidic CD platforms are utilized to perform different biological processes and chemical analyses. In general, a microfluidic CD implements the centrifugal force that is created by the spinning of the platform to pump liquid through the microfluidic network of chambers and channels. Over the last few decades, a wide range of active and passive valving methods were proposed and tested on various microfluidic platforms. Most of the presented valves are too complex to design and involve lengthy fabrication processes. In this paper, easy to fabricate air and liquid check valves for centrifugal microfluidic platforms are presented: a Terminal Check Valve (TCV) and a Bridge Check Valve (BCV). To understand the characteristic of the proposed valves, theoretical and experimental studies are conducted. Moreover, to test the effectiveness of these valves, liquid swapping is demonstrated by integrating TCV and BCV chips with thermo-pneumatic (TA) pumping on a CD. The valves are shown to accurately control flow direction which makes them an excellent choice for a variety of complex microfluidic processes. The experimental and theoretical results also indicate that these valves require low pressure for actuation. Furthermore, the theoretical results confirm the ability to adjust the required actuation pressure by changing the valve chip size. Finally, as a proof of concept for implementing the check valves on a biological application, an enzyme linked immunosorbent assays (ELISA) is performed. The result shows that the TOT and BCV valving chips enhance the operating range of the processes that can be performed on the microfluidic CD. (C) 2014 Elsevier B.V. All rights reserved.